Evaluating technology integration in education: a framework for professional development - Yacoub Siyam; Nur Siyam; Malak Hussain; Omar Alqaryouti (Discover Education)
Abstract The integration of technology in education is essential for enhancing learning experiences and preparing students for a technology-driven world. However, many teachers lack the necessary skills and confidence to effectively incorporate technology into their classroom practices. This paper investigates the impact of technology-related professional development (PD) on teachers' self-reported technology competencies and their application of technology in classroom practices, addressing the critical need for effective PD programs that can bridge this gap. The study involved the development and administration of a self-reported Information and Communication Technology (ICT) competencies survey, the observation of classroom practices using a custom-developed observation tool, and the implementation of a comprehensive PD program followed by a subsequent reassessment using the same instruments. The findings demonstrate significant improvements in teachers' self-reported competencies and classroom practices following the PD sessions. The validated self-rating technology skills survey and classroom observation tool proved to be reliable and effective measures for assessing teachers' ICT competencies and the integration of technology in teaching. The study underscores the necessity of well-designed PD programs that incorporate active learning, collaboration, and sustained support to enhance teachers' technology integration skills.